2022
DOI: 10.3390/md20080484
|View full text |Cite
|
Sign up to set email alerts
|

Two Foreign Antimicrobial Peptides Expressed in the Chloroplast of Porphyridium purpureum Possessed Antibacterial Properties

Abstract: To solve the problem of antibiotic abuse in aquaculture and to utilize the application potential of antimicrobial peptides (AMPs), a chloroplast transformation system of Porphyridium purpureum was successfully constructed for effectively expressing two exogenous AMPs. The endogenous fragments of 16S rDNA/trnA-23S rDNA were used as flanking fragments for the homologous recombination in the chloroplast genome. Two AMPs encoded by the transformation vector were controlled by the native promoter psbB in a polycist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…With their capacity to fend off and defend against diseases, cyanobacteria and microalgae are valuable sources of such compounds [ 23 ]. Alkaloids, fatty acids, indoles, macrolides, peptides, phenols, pigments, and terpenes are some of the antibacterial substances created by cyanobacteria [ 24 , 25 ]. The kind of algae, the extractor, and the concentration of the extract all affect the antibacterial potential of cyanobacteria, macro-, and microalgae [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…With their capacity to fend off and defend against diseases, cyanobacteria and microalgae are valuable sources of such compounds [ 23 ]. Alkaloids, fatty acids, indoles, macrolides, peptides, phenols, pigments, and terpenes are some of the antibacterial substances created by cyanobacteria [ 24 , 25 ]. The kind of algae, the extractor, and the concentration of the extract all affect the antibacterial potential of cyanobacteria, macro-, and microalgae [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The genus Pennisetum contains remarkable natural bioactive components and is frequently used for therapeutic purposes such as the treatment of dysentery, fever, diabetes and abdominal pain (Ojo et al, 2022). Previous studies have shown that P. purpureum has some biological (Ujang et al, 2021;Han et al, 2022) and digestibility properties (Wahyono et al, 2022). Very few studies have been carried out on the anti-inflammatory, antioxidant and antimicrobial activities of P. purpureum leaves.…”
Section: Introductionmentioning
confidence: 99%